Dizziness Evaluation and Characterisation of Patients with Posterior Circulation Stroke in the Emergency Department; a Case Series Study - Saro- Buendía, Miguel; Torres García, Lidia; Jaramillo Angel, Natalia; Mellidez Acosta, Raul; Cabrera Guijo, Javier; Bancalari Díaz, Catalina; García Piñero, Alfonso; Pérez Guillén, Vanesa; Armengot Carceller, Miguel (Archives of Academic Emergency Medicine, 2023)
Introduction: Dizziness is a common scenario in the Emergency Departments (EDs). Among dizziness underlying causes, the posterior circulation stroke is especially relevant due to its mobimortality and concerning misdiagnosis rates. Therefore, we conducted this study to assess dizziness evaluation and baseline characteristics of patients with PS in the ED. Methods: We conducted a 3-year retrospective observational study on PS cases confirmed by magnetic resonance imaging (MRI). Concretely, we analysed the demographic profile of these patients, the initial PS clinical presentation, and diagnostic workup (with emphasis on dizziness evaluation) performed at the ED. Results: During the study period, 85 cases were registered. Risk factors for cardiovascular disease were present in 85.5% and previous visits to the ED due to dizziness were recorded in 16.5%. The main clinical presentation was dizziness, concretely as an acute vestibular syndrome (38.8%) with additional neurological signs or symptoms (80%). Evaluation by the otolaryngologist on call was requested in less than 10% of the cases and included the HINTS protocol use with a sensitivity of 100% for central nervous system underlying causality. A brain CT study was always performed with a sensitivity of 27%. However, 96.47% of patients were primarily admitted to the Neurology hospitalization ward and MRI was always performed in a mean time of 3.21 days confirming the diagnosis. Conclusions: Dizziness is the most frequent symptom of PS. Patients usually present an AVS (associated with additional N-SS or not) and HINTS bedside examination is the most adequate protocol to differentiate a PS from other AVS causes until the diagnostic confirmation via MRI. Interestingly, mainly otolaryngologists seem to use HINTS. However, the use of CT is widespread despite its poor value.